Improved Screening Test for Idiopathic Infantile Hypercalcemia Confirms Residual Levels of Serum 24, 25‐(OH)2D3 in Affected Patients. (21st April 2017) - Kaufmann, Martin; Morse, Nicole; Molloy, Billy Joe; Cooper, Donald P; Schlingmann, Karl Peter; Molin, Arnaud; Kottler, Marie Laure; Gallagher, J Christopher; Armas, Laura; Jones, Glenville
ABSTRACT: CYP24A1 mutations are now accepted as a cause of idiopathic infantile hypercalcemia (IIH). A rapid liquid‐chromatography tandem mass spectrometry (LC‐MS/MS)‐based blood test enabling measurement of the 25‐OH‐D3 :24, 25‐(OH)2 D3 ratio (R) can identify IIH patients on the basis of reduced C24‐hydroxylation of 25‐OH‐D3 by CYP24A1 in vivo. Although values of this ratio are significantly elevated in IIH, somewhat surprisingly, serum 24, 25‐(OH)2 D3 remains detectable. The current study explores possible explanations for this including: residual CYP24A1 enzyme activity in individuals with certain CYP24A1 genotypes, expression of alternative C24‐hydroxylases, and the possibility of isobaric contamination of the 24, 25‐(OH)2 D3 peak on LC‐MS/MS. We employed an extended 20‐min run time on LC‐MS/MS to study serum vitamin D metabolites in patients with IIH due to mutations of CYP24A1 or SLC34A1 ; in unaffected heterozygotes and dialysis patients; in patients with vitamin D deficiency; as well as in normal subjects exhibiting a broad range of 25‐OH‐D levels. We identified 25, 26‐(OH)2 D3 as a contaminant of the 24, 25‐(OH)2 D3 peak. In normals, the concentration of 24, 25‐(OH)2 D3 greatly exceeds 25, 26‐(OH)2 D3 ; however, 25, 26‐(OH)2 D3 becomes more significant in IIH with CYP24A1 mutations and in dialysis patients, where 24, 25‐(OH)2 D3 levels are low when CYP24A1 function is compromised. Mean R in 30 IIH‐CYP24A1 patients was 700 (range, 166 to 2168; cutoff = 140) as compared with 31 in 163 controls. Furthermore, patients possessing CYP24A1 L409S alleles exhibited higher 24, 25‐(OH)2 D3 levels and lower R (mean R = 268; n = 8) than patients with other mutations. We conclude that a chromatographic approach which resolves 24, 25‐(OH)2 D3 from 25, 26‐(OH)2 D3 produces a more accurate R that can be used to differentiate pathological states where CYP24A1 activity is altered. The origin of the residual serum 24, 25‐(OH)2 D3 in IIH patients appears to be multifactorial. © 2017 American Society for Bone and Mineral Research.